Breast Cancer Epidemiology and Survival Analysis of Shenyang in Northeast China: A Population-Based Study from 2008 to 2017 - Hongbo Su; Xun Li; Yi Lv; Xueshan Qiu (Hindawi-Wiley, 2022)
Background. To investigate the status of breast cancer incidence, trends, and survival in women in urban Shenyang from 2008-2017 using large Cancer Registry data. Methods. Breast cancer incidence and mortality data were abstracted from the Shenyang Cancer Registry between 2008 and 2017. The crude and age-standardized incidence and mortality rates were calculated for each year. Average annual percentage changes (AAPC) were used to describe the change over time. Results. A total of 14,255 out of 18,782,956 women were diagnosed with breast cancer between 2008 and 2017 in urban Shenyang. The overall crude and age-standardized incidences were 75.89 and 43.42 per 100,000, respectively. The crude incidence increased from 61.93 per 100,000 in 2008 to 90.07 per 100,000 in 2017, with an AAPC of 5.10%. The crude mortality increased from 11.41 per 100,000 in 2008 to 17.29 per 100,000 in 2017, with an AAPC of 4.60. The highest age-specific incidence occurs in the 55-59 year age group at a rate of 140.67 per 100,000. During the study period, 2,710 women died from breast cancer. The overall crude and age-standardized mortality rates were 14.43 and 7.43 per 100,000, respectively. The highest age-specific mortality occurs at 80-84 years old at a rate of 57.57 per 100,000. The 3-year and 5-year survival rates for female breast cancer in urban Shenyang from 2008 to 2013 were 85.61% and 77.39%, respectively, and both declined with age. Conclusion. The incidence and mortality rates of breast cancer in Shenyang increased over time. Screening and control strategies should be enhanced, especially for perimenopausal females.